2018
DOI: 10.1002/14651858.cd001746.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Family and carer smoking control programmes for reducing children's exposure to environmental tobacco smoke

Abstract: Family and carer smoking control programmes for reducing children's exposure to environmental tobacco smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 184 publications
0
83
0
Order By: Relevance
“…Noticeably, exposure to SHS is very common in Asia (Drope et al, ), with approximately 53.8–63.5% of Asian adolescents 12–15 years of age reporting exposure to SHS, with the two main sources of SHS being home and public places (Xi et al, ). Thus, family interventions, including helping parents to quit smoking earlier and reducing exposure to SHS at home are needed to improve both family members' health and reduce the lifetime smoking risk of children (Behbod, Sharma, Baxi, Roseby, & Webster, ; Mays et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, exposure to SHS is very common in Asia (Drope et al, ), with approximately 53.8–63.5% of Asian adolescents 12–15 years of age reporting exposure to SHS, with the two main sources of SHS being home and public places (Xi et al, ). Thus, family interventions, including helping parents to quit smoking earlier and reducing exposure to SHS at home are needed to improve both family members' health and reduce the lifetime smoking risk of children (Behbod, Sharma, Baxi, Roseby, & Webster, ; Mays et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Waddington (2009) Water, sanitation, and hygiene interventions to combat childhood diarrhoea in developing countries Hygiene education (21 studies); e.g. Buck (2017) Promoting handwashing and sanitation behaviour change in low-and middle-income countries A mixed-method systematic review Prevention of outdoor and indoor air pollution (one study), which is the smoking-related study; (Behbod, 2018) Family and carer smoking control programmes for reducing children's exposure to environmental tobacco smoke.…”
Section: What Interventions Are Included For a Safe And Clean Environmentioning
confidence: 99%
“…A range of interventions have been developed to promote smoke-free homes (SFHs), for example using counselling approaches, feedback of a biological measure of children's SHS exposure, school-based strategies and educational materials. However, reviews of interventions to reduce SHS in households with children have concluded that there is insu cient evidence to recommend any speci c approach [14,15].…”
Section: Introductionmentioning
confidence: 99%